The Effect of Red Ginger Extract (Zingiber officinale Roscoe, Zingiberaceae) on Analgesia in Male White Rats (Rattus norvegicus) Wistar Strain with Head Injuries - Boyke Marthin Simbolon; Nurul Hasanah SB; Elviyanti Br Tarigan (International Journal of Health and Pharmaceutical (IJHP), 2025)
Head injury represents a significant clinical challenge requiring effective pain management strategies. This study examined the analgesic effects of red ginger extract on head injury in male Wistar rats. The research employed an experimental post-test only control group design with five treatment groups (n = 25 subjects; n = 5 per group). Group K1 received piroxicam (40 mg per 200 g body weight); K2 served as untreated control; groups K3, K4, K5 received red ginger extract at 50, 100, and 150 micrograms per kilogram of body weight per day respectively. Behavioral pain assessment was conducted on days 8 and 21 post-injury using standardized ethological procedures. Statistical analysis utilized Kruskal-Wallis test with post-hoc Mann-Whitney U comparisons. Results demonstrated that K4 (100 μg/kg/day) achieved the lowest mean rank (8.00), indicating superior analgesic efficacy compared to other groups. K4 exhibited comparable effectiveness to piroxicam (K1, mean rank 10.00) and superior outcomes to untreated controls (K2, mean rank 21.60). Selective COX-2 inhibition and inflammatory cytokine reduction mediated these effects. The optimal dose of red ginger extract (100 μg/kg/day) provides significant neuroprotection and may serve as an alternative pain management approach in developing healthcare contexts.